A Case of Hepatic Fasciolosis Presented with Prolonged Fever in Southern Iran - Anahita Sanaei Dashti; Amir Nasimfar; Alireza Showraki; Bita Gerami-Zadeh (Tehran University of Medical Sciences, 2015)
Human fasciolosis is deemed as an emerging/re-emerging infection, hence making it an important human parasitic disease. In contrast to northern parts of Iran, human cases of fasciolosis in southern Iran are rare and sporadic. We report a sporadic case of fasciolosis in southern Iran (Fars Province) who presented with prolonged fever. Our report could suggest that there might be new foci emerging in the region, which indicates the need for further investigations.